2002
DOI: 10.1103/physrevb.65.153310
|View full text |Cite
|
Sign up to set email alerts
|

Polariton lasing by exciton-electron scattering in semiconductor microcavities

Abstract: The relaxation bottleneck present in the dispersion relation of exciton polaritons in semiconductor microcavities has prevented the realization of low threshold lasing based on exciton-polariton condensation. Here we show theoretically that the introduction of a cold electron gas into such structures induces efficient electronpolariton scattering. This process allows the condensation of the polaritons accumulated at the bottleneck to the final emitting state with a transition time of a few picoseconds, opening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
121
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(128 citation statements)
references
References 21 publications
4
121
1
2
Order By: Relevance
“…This is attributed to the difference in the efficiency of the free electron scattering mechanism as a function of temperature. 55 For the direct electrical pumping geometry, the electron distribution does not depend on T latt since electrons are not thermalized, thus leading only to slight changes in the free electron scattering rate with temperature and thereby explaining the weak δ opt (T ) variation dis-played in Figs. 4(a) and 4(c).…”
mentioning
confidence: 99%
“…This is attributed to the difference in the efficiency of the free electron scattering mechanism as a function of temperature. 55 For the direct electrical pumping geometry, the electron distribution does not depend on T latt since electrons are not thermalized, thus leading only to slight changes in the free electron scattering rate with temperature and thereby explaining the weak δ opt (T ) variation dis-played in Figs. 4(a) and 4(c).…”
mentioning
confidence: 99%
“…One particular difference shown by these systems is that the quasiparticles have finite lifetimes, and as a result, they can be made to form condensates out of equilibrium, which are best understood as a steady state balance between pumping and decay, rather than true thermal equilibrium. The effects of pumping and decay in these condensates have been the subject of several recent works [5,11,12,13,14,15,16,17,18,19,20] which have shown that even when collisions can rapidly thermalise the energy distribution of a system, there may yet be noticeable effects associated with the energy scale introduced by the pumping and decay.The Gross-Pitaevskii equation (GPE) has been applied to successfully describe many features of equilibrium condensates when far in the condensed regime, including density profiles, the dynamics of vortices, hydrodynamic modes -see e.g. [21] and Refs.…”
mentioning
confidence: 99%
“…Despite their short life time, they can thermalize to a quasi-thermal (Bose) distribution [9,10,11,12,13] which can in principle allow the polariton gas to undergo a Berezinskii-Kosterlitz-Thouless phase transition towards a superfluid state [14,15,16]. In CdTe or GaN cavities, this superfluid behavior of the condensed phase was not observed because of the presence of a strong in plane disorder which tends to localize the condensate, leading to the formation of a glassy phase [17].…”
Section: Introductionmentioning
confidence: 99%